The Role of the Immune Response in Chlamydia trachomatis Infection of the Male Genital Tract: A Double-Edged Sword - Redgrove, Kate A.; McLaughlin, Eileen A. (Frontiers in Immunology, 2014)
Chlamydia trachomatis (CT) is the most prevalent bacterial sexually transmitted infection in the world, with more than 100 million cases reported annually. While there have been extensive studies into the adverse effects that CT infection has on the female genital tract, and on the subsequent ability of these women to conceive, studies into the consequences on male fertility have been limited and controversial. This is in part due to the asymptomatic nature of the infection, where it is estimated that 50% of men with Chlamydia fail to show any symptoms. It is accepted however, that acute and/or persistent CT infection is the causative agent for conditions such as urethritis, epididymitis, epididymo-orchitis and potentially prostatitis. As with most infections, the immune system plays a fundamental role in the body’s attempts to eradicate the infection. The first and most important immune response to Chlamydia infection is a local one, whereby immune cells such as leukocytes are recruited to the site of infections, and subsequently secrete pro-inflammatory cytokines and chemokines such as Interferon gamma. Immune cells also work to initiate and potentiate chronic inflammation through the production of reactive oxygen species (ROS), and the release of molecules with degradative properties including defensins, elastase, collagenase, cathespins and lysozyme. This long-term inflammation can lead to cell proliferation (a possible precursor to cancer), tissue remodeling and scarring, as well as being linked to the onset of autoimmune responses in genetically disposed individuals. This review will focus on the ability of the immune system to recognize and clear acute and persistent chlamydial infections in the male genital tract, and on the paradoxical damage that chronic inflammation resulting from the infection can cause on the reproductive health of the individual.